Localization of treatment‐resistant areas in patients with psoriasis on biologics. (7th May 2019) - Hjuler, K.F.; Iversen, L.; Rasmussen, M.K.; Kofoed, K.; Skov, L.; Zachariae, C.
Summary: Background: Traditionally, psoriasis in certain body sites such as the scalp, nails, palms, soles and intertriginous areas has been acknowledged as difficult to treat. Objectives: To investigate the body location of treatment‐resistant psoriasis in patients treated with biologic agents in real‐world clinical practice, and to study the association between localization and quality of life. Methods: This was an observational, noninterventional, study. We investigated the skin and/or nail location of treatment‐resistant psoriasis in patients with moderate‐to‐severe psoriasis treated for > 6 months with biologic agents. A partial or good response to treatment was defined as having a Psoriasis Area and Severity Index (PASI) score ≥ 1 and ≤ 5. Experienced PASI assessors used a uniform data collection form in which the body area was divided into 26 regions and 20 nails. Results: We included 146 patients with chronic plaque‐type psoriasis (109 men, 74·7%, mean ± SD age 49·8 ± 13·7 years), with a median PASI score of 2·4 (interquartile range 1·2–3·2). The median PASI reduction from treatment initiation was 86·1% (interquartile range 78·1–91·3). The most common site of recalcitrant psoriasis was the anterior lower leg [49·3%; 95% confidence interval (CI) 41·2–57·4]. Further common sites of recalcitrant psoriasis were the posterior lower leg (24·7%; 95% CI 17·7–31·6), elbow (35·6%; 95% CI 27·8–43·4) and the scalp (19·2%; 95% CI 12·8–25·6%). No association between Dermatology Life Quality Index and specific areas of recalcitrant psoriasis were observed. Conclusions: In real‐world clinical practice, the most common sites of recalcitrant psoriasis in patients treated with biologic agents are the anterior lower leg, posterior lower leg and elbows. Recalcitrant psoriasis in no specific area caused a greater impact on quality of life than any other area. Abstract : What's already known about this topic? Psoriasis in some areas of the body can be difficult to treat. The sites that are known to be difficult to treat are the scalp, nails, palms, soles and the intertriginous areas, particularly if only local treatment is used. Whether this is also the case with biologic treatment is not known. What does this study add? This study demonstrates that treatment‐resistant areas are primarily the shins, and thereafter the elbows and the posterior part of the lower legs. This small study does not support the impression that residual psoriasis in any particular area influences the quality of life more than any other area. Linked Comment:  Belinchón. Br J Dermatol 2019; 181 :242–243 . Respond to this article